2004
DOI: 10.2737/rmrs-gtr-120
|View full text |Cite
|
Sign up to set email alerts
|

Science basis for changing forest structure to modify wildfire behavior and severity

Abstract: Fire, other disturbances, physical setting, weather, and climate shape the structure and function of forests throughout the Western United States. More than 80 years of fire research have shown that physical setting, fuels, and weather combine to determine wildfire intensity (the rate at which it consumes fuel) and severity (the effect fire has on vegetation, soils, buildings, watersheds, and so forth). Millions of acres of forestlands (mainly in dry forests dominated by ponderosa pine and/or Douglas-fir) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
304
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 261 publications
(311 citation statements)
references
References 74 publications
(59 reference statements)
3
304
0
4
Order By: Relevance
“…Current findings suggest treatment effects on fire severity are mostly confined to treated areas [3], but theory suggests a dense network of treatments might slow fire spread and reduce intensity, yielding a landscape-scale effect on fire severity [42]. However, empirical evidence of severity reduction was seen in the lee of only three of several dozen treatments in two Arizona wildfires [43].…”
Section: Relaxing the Assumptions And Some Caveatsmentioning
confidence: 99%
See 3 more Smart Citations
“…Current findings suggest treatment effects on fire severity are mostly confined to treated areas [3], but theory suggests a dense network of treatments might slow fire spread and reduce intensity, yielding a landscape-scale effect on fire severity [42]. However, empirical evidence of severity reduction was seen in the lee of only three of several dozen treatments in two Arizona wildfires [43].…”
Section: Relaxing the Assumptions And Some Caveatsmentioning
confidence: 99%
“…The duration of post-treatment fuel reduction, n, likely varies regionally with factors affecting vegetation re-growth rates, but fuels in western U.S. forests generally return to pretreatment levels in 10-20 years [3,7]. To estimate the upper limit of treatment effectiveness, we assume n = 20 years.…”
Section: The Analytical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Zielinski et al (2006) and GarcĂ­a-Feced et al (2011) demonstrated that forest structure information was critical for mapping the habitat of Pacific fisher (Pekania pennanti) and California spotted owl (Strix occidentalis occidentalis). Graham et al (2004), Agee and Skinner (2005) and Peterson et al (2005) all pointed to the important role that forest structure has on wildfire behavior and argued that modifying forest structure through forest treatment might be necessary to reduce fire risk in many dry conifer forest types. Developing methods to integrate structure information into the process of vegetation mapping is an important area of research.…”
Section: Introductionmentioning
confidence: 99%